(untitled) (Research, Society and Development, 2021)
Death is an enigma of the soul and of life, and for people to understand the process and representations of individuals about death, it would perhaps mean understanding the concept of life and, when it occurs in pediatric emergency, such feelings tend to intensify, for, even though it is an unavoidable fact, it is considered a natural event at a later age. This is a bibliographic research with a qualitative approach and descriptive character that aims to describe the process of death and dying in the pediatric emergency sector; identify the perception and performance of nurses in the process of death and dying in pediatric emergency and also reflect on the coping strategies of nurses in the process of death and dying in pediatric emergency. To meet the methodological aspects, the Virtual Health Library was used, in the LILACS, BDENF and Google Scholar databases, with a time frame from 2015 to 2020. It is concluded that hospital institutions that have the pediatric emergency sector create psychological support mechanisms, training, as well as a room in the sector for group discussions on issues related to the death process of children hospitalized in the emergency room that cause suffering for nurses and their staff.